Performance Evaluation of Fiber Optical Sensors for Health Monitoring of Civil Structures - Kaur, Gurpreet (My University, 2019)
The presence of optical devices has made their deep place in our everyday life through various processes like sensing, communication, entertainment, fashion, security, medical diagnosis, industrial growth etc. In recent years, optical fiber has found major application in sensor technology due to inherent advantages such as immunity to electromagnetic interference, electrical isolation, chemical passivity, small size, low weight, long range operation, and ability to sense variety of measurands. Nowadays, optical sensors are commercially available to monitor the health of civil structures in real time scenario but still it is required to enhance the sensitivity. Multiparameter sensing using single sensor is an open area of research, so on existing optical sensors many things can be investigated to further enhance the performance of optical sensors. With same motivation, in this thesis, several optical sensors are proposed to sense the important parameters i.e. strain, vibration, temperature, refractive index, portlandite etc. for civil structures with high sensitivity and speed. To achieve the first objective, an optical refractive index (RI) fiber Bragg grating (FBG) sensor is proposed to monitor the chemical concentrations i.e. calcium hydroxide Ca(OH)2 and calcium analogue of brucite Mg(OH)2 which can introduce the corrosion and spalling in civil structures. The motivation to sense these parameters is that if the undesired level of these parameters can detect at early stage then structure against corrosion and spalling can be protected. At first stage, to sense Ca(OH)2 and Mg(OH)2, cladding etched sensor with uniform grating is used and it is observed that the sensitivity is required to enhance further. In second stage, to address this problem, on the same sensor a layer of indium tin oxide (ITO) is coated and observed the wavelength shift of 12 nm and 10 nm with respect to Ca(OH)2 and Mg(OH)2 On the other hand, with respect to same parameters, cladding etched FBG sensor induced wavelength shift of 8 nm and 6 nm only. The OptiFDTD software was used to perform these investigations with chemical concentrations. For better clarity, several experiments have been performed on different civil structures using FBG sensor (having uniform grating). Concrete and steel beams with different dimensions are considered to perform these experiments. The load is applied and release by computer servo-controlled material testing machine and hanger, respectively. As ii expected, the wavelength shifts are observed with respect to the change in strain values. The testing is stopped when the deformation (in term of cracks) is observed on structures. From the experiments on FBG sensor, maximum 7 nm of wavelength shift is observed which needs to be improved. These experiments have been performed by using FBG sensors, Interrogator, power supply, ENLIGHT sensing analysis software for PC and ethernet cables of Micron Optics Pvt. Ltd. Further, the aim was to enhance the sensitivity and range of the FBG sensor. To achieve this aim, in first step, a genetic algorithm (GA) is used for multiparameter optimization. Three important parameters (i.e. Poisson’s Ratio (PR), photo-elastic coefficient P11, and photo-elastic coefficient P12) of FBG sensor are selected which are processed by GA to get best combination yielding large wavelength shift. It is observed that the optimized FBG sensor provides enormous wavelength shift of 38.16 nm with respect to PR of 1.94, photoelastic coefficient P11 of 1.994, and photoelastic coefficient P12 of 1.8103. Apart from optimization, other possibilities such as grating shapes, grating length and core refractive indexes of FBG have been examined to enhance the sensitivity of FBG sensor. It is observed that the FBG sensor with uniform grating shape having 1.46 of refractive index and 50000 µm of grating length provides high sensitivity. These simulations and numerical calculations have been performed when 0.2145 (1/µε) strain is applied on FBG sensor. This study establishes the design, characterization and optimization of highly sensitive optical sensors for health monitoring of civil structures. Most of the research findings of this thesis have been published in various International referred Journals and International Conference as per the list at page (5).
Keywords: optical sensor; FBG; optical fiber; civil structure